Length-Weight Relationship and the Condition Factor of some Important Estuarine Fish Species from Kakum Estuary of Ghana (Ghana Journal of Science, Technology and Development, 2022)
This study assessed the length-weight relationships and the condition factors of nine commercial and abundant fish species namely Liza dumerilli, Mugil curema, Liza falcipinnis, Mugil bananensis, Lutjanus goreensis, Lutjanus fulgens, Sardinella aurita, Caranx hippos, and Eucinostomus melanopterus from the Kakum River Estuary. This study was conducted from November 2016 to April 2017 to provide primary information about the biometrics, the length-weight model parameters, and the state of well-being of fish species inhabiting the Kakum Estuary. Sampling was done monthly using a mini boat of 9 m long with a depth of 1.5 m for both diurnal (06:00, 10:00, 14:00, 18:00, 06:00 h) and nocturnal (22:00, 02:00 h) periods with a medium-mesh cast net of 20 mm stretched. Sampling was done within thirty (30) minutes on all sampling times. The total length of the species from the estuary ranged from 2.2 cm in Liza dumerilli to 29.8 cm in Mugil curema while the total weight ranged from 0.2 g to 251 g in Mugil curema. The slope b values of the species varied from 2.3787 for Liza dumerilli to 3.1009 for Eucinostomus melanopterus. Three species from the Kakum Estuary exhibited negative allometric growth and 6 species were growing isometrically.  The mean condition factors of the fish species ranged from 0.82 Â± 0.36 (SD) in Sardinella aurita to 1.82 Â± 0.23 (SD) in Lutjanus goreensis. The results of the present study provide essential input parameters for further assessment of the species standing stock biomass.